Analysis of Factors Influencing Purchasing Decisions for Hanasui Lipstick - Ersa Diandra Ixania; Khotim Fadhli (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Study is used to understand the influence of price, brand image, and beauty influencer reviews on the purchase decision of Hanasui lipstick in female students of the Economics Faculty, KH. Abdul Wahab Hasbullah University. The quantitative approach is a kind of study that takes a large amount of data, because of the very wide population of respondents. The study involved a population that was obtained from 112 students Faculty of Economics KH. A Wahab Hasbullah University who has bought and used Hanasui lipstick. The Slovin formula was used to calculate the study's sample size., the respondents use the Purposive Sampling technique. The questionnaire data was subsequently analyzed using SPSS version 26. The research results state the price did not affect the purchasing decision of Hanasui lipstick on students of the Economics Faculty, KH. Abdul Wahab Hasbullah University. Brand image affected the purchasing decision of Hanasui lipstick on students of the Economics Faculty, KH. Abdul Wahab Hasbullah University. Beauty influencer reviews affected the purchasing decision of Hanasui lipstick on students of the Economics Faculty, KH. Abdul Wahab Hasbullah University. Price, Brand image, and Beauty influencer reviews simultaneously has a positive and significant influence on purchasing decisions had a positive and significant effect on the purchasing decision of Hanasui lipstick on students of the Economics Faculty, KH. Abdul Wahab Hasbullah University.